IMPLEMENTASI KEBIJAKAN PENGELOLAAN PERSAMPAHAN DI DINAS KEBERSIHAN KOTA MANADO - -, Murdiningsih -; Pangkey, Masje; Rompas, Welson (Sam Ratulangi University, 2014)
ABSTRACT Trash has become a national issue that management needs to be done in a comprehensive and integrated headwaters downstream waste management necessary legal certainty, clarity of responsibility and authority of the government, local government, the role of the community and waste management can proceed professional, effectively and efficiently. So the president issued Law Decree No.18 of 2008 on Waste Management which aims to reduce the waste problem in Indonesia. Waste management aims to serve a city of garbage generated population, which indirectly contribute to maintaining public health and create a cleaner environment. To support the establishment of the provincial capital of Manado as a clean, healthy, comfortable, beautiful and environmentally friendly. Mayor of Manado making policy on Waste Management in the city of Manado, the policy was issued to strengthen the Regional Regulation No. 07 Year 2006 concerning Manado Waste Management and General Services Levies. In this study using the model of George C. Edwards III where implementation can be started from the abstract state and a question of whether the conditions for policy implementation to be successful is communication, communication is between implementing policies / programs with community target groups. Resources, is the human resources and financial resources available or provided for the implementation of policies / programs. Disposition, is characteristic that attaches to the executive like honesty, commitment and democratic attitudes. Bureaucratic structure, is the mechanism (SOP) and the structure of the organization implementing the policy. This study uses a qualitative descriptive approach through interviews of 11 informants, observation and tracking documents and research is assisted by an additional instrument in the form of a list of guidelines for interviewing, recording devices (Hand phone) and stationery. The results showed that the overall waste management policy in Manado City Sanitation Department has shown a pretty good rate, in other words the implementation of solid waste management in terms of freight has been carried out effectively, but seen from the time of completion is still not efficient, since there are often delays garbage carry. Over all results of the interview on the results of the implementation of the waste management policy to the conclusion that the success rate in Waste Management Policy Implementation in Manado City Sanitation Department is quite good. Keywords: Implementation of Waste Management Policy